Quantum-dot Based Light-emitting Diodes - Sasani Ghamsari, Morteza (IntechOpen, 2017)
Quantum dot-based light emitting diodes were assigned to bringing together the latest and most important progresses in light emitting diode (LED) technologies. In addition, they were dedicated to gain the perspective of LED technology for all of its advancements and innovations due to the employment of semiconductor nanocrystals. Highly selective, the primary aim was to provide a visual source for high-urgency work that will define the future directions relating to the organic light emitting diode (OLED), with the expectation for lasting scientific and technological impact. The editor hopes that the chapters verify the realization of the mentioned aims that have been considered for editing of this book. Due to the rapidly growing OLED technology, we wish this book to be useful for any progress that can be achieved in future.